2006
DOI: 10.1002/pssb.200669199
|View full text |Cite
|
Sign up to set email alerts
|

Single‐walled carbon nanotubes/polycarbonate composites: basic electrical and mechanical properties

Abstract: The focus of this paper is to investigate the electrical conductivity and the mechanical properties of single-walled carbon nanotubes/polycarbonate composites. Two different direct incorporating methods were applied. In the first method PC and SWCNTs were mixed with different ratios in a small scale conical twin screw extruder. Here, additional variations in the feeding of the filler material were tested in order to improve the state of dispersion of the melt mixing method. The second one is the coagulation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 8 publications
3
59
1
Order By: Relevance
“…If nanofillers are randomly distributed, then the mean average distance (d) among the nanofillers would be barrier width. This mean average distance is considered, in the first approximation, to be directly proportional to the nanofillers concentration in weight, p -1/3 and can be expressed by the following Equation (10) [24]: (10) Thus, the combination of the Equations (9) and (10), shows that tunneling assisted conductivity (log! DC ) is directly proportional with p -1/3 and expressed by the following Equation (11): (11) Figure 1c shows the linear variation of log!…”
Section: Results and Discussion 41 Electrical Analysis 411 DC Comentioning
confidence: 99%
See 2 more Smart Citations
“…If nanofillers are randomly distributed, then the mean average distance (d) among the nanofillers would be barrier width. This mean average distance is considered, in the first approximation, to be directly proportional to the nanofillers concentration in weight, p -1/3 and can be expressed by the following Equation (10) [24]: (10) Thus, the combination of the Equations (9) and (10), shows that tunneling assisted conductivity (log! DC ) is directly proportional with p -1/3 and expressed by the following Equation (11): (11) Figure 1c shows the linear variation of log!…”
Section: Results and Discussion 41 Electrical Analysis 411 DC Comentioning
confidence: 99%
“…PC has high impact resistance, toughness, dimensional stability and good optical clarity, and is mostly used in many engineering applications. PC has been modified by blending with various polymers for different applications and compounding with different kinds of CNTs to enhance the electrical, mechanical and thermal properties of the PC [9][10][11][12]. For instance, Wu et al [9] have observed electrical conductivity of 2!10 -8 S·cm -1 with 2 wt% loading of MWCNT in melt blended PC/MWCNT nanocomposites, prepared by diluting solution blended PC/carboxylic acid functionalized MWCNT (10 wt%) mixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of graphite nanoparticles and carbon black the content was not sufficient to reach the percolation threshold, therefore no conduction network was formed and SE was low. Depending on carbon black properties percolation thresholds in polycarbonate matrix were found to be from 5 to 10 w% [9], and SE values of 10 dB for carbon black/rubber composites were measured at loadings higher than 30 w% [4]. Concerning CSCNT, their high electrical conductivity together with high aspect ratio (ratio of length to diameter is more than 20) and uniform dispersion in the PMMA can lead to formation of conducting network even at very low loadings (less than 1 w%), in the same way as was observed for MWCNT [5,10] and SWCNT [9], and as a result to the higher SE.…”
Section: Compositementioning
confidence: 99%
“…Depending on carbon black properties percolation thresholds in polycarbonate matrix were found to be from 5 to 10 w% [9], and SE values of 10 dB for carbon black/rubber composites were measured at loadings higher than 30 w% [4]. Concerning CSCNT, their high electrical conductivity together with high aspect ratio (ratio of length to diameter is more than 20) and uniform dispersion in the PMMA can lead to formation of conducting network even at very low loadings (less than 1 w%), in the same way as was observed for MWCNT [5,10] and SWCNT [9], and as a result to the higher SE. Comparing to the data for MWCNT / polypropylene composites, reported in [5], the values of SE measured in the present work for CSCNT/PMMA composites are lower, that can be explained by lower electrical conductivity of CSCNT in comparison with MWCNT, but this requires additional studies.…”
Section: Compositementioning
confidence: 99%